ASSOCIATION OF VITAMIN D STATUS WITH CARCINOMA ESOPHAGUS AND ITS OUTCOME - Dr.Shabir Ahmad Dar; Dr.Shah Syed Mahmood Kadri; Dr.Touseef Ahmad Mir; Dr.Zaffar Iqbal Kawoosa; Dr.Sajad (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
INTRODUCTION:In India esophageal carcinoma is most common malignancy involving gastrointestinal tract in Karnataka, Kerala, Tamil Nadu and Assam. In Kashmir esophageal carcinoma is ranking at number one, but there is scarcity of epidemiological studies in this regard AIM:To study vitamin D level in patients with carcinoma esophagus. METHODOLOGY:All patients who were registered at Regional cancer centre, as a case of carcinoma esophagus were enrolled in the study. This was a prospective case control study. Study group was divided into two groups-case and control group. • Cases included patients with histological confirmation of carcinoma esophagus. (Group A) • Control group included healthy member from the family. (Group B) Blood samples were taken from the patients and control group and vitamin D levels were calculated by ELISA method. • Inclusion criteria • All patients with histological confirmation of carcinoma esophagus were included in the study. • Exclusion criteria • Patients who had co-morbid conditions . • Patients who had undergone surgery. Data Analysis: Data was analysed using SPSS software version 20. OBSERVATIONS : In this case control study 165 cases and 142 controls participated. The mean age of cases and controls was 60.74±74 and 54.78±9.29 years respectively.52.7 % cases were smokers as against controls 33.1% and the difference was statistically significant (p<0.05).Majority of the patients (86.1%) had grade I dysphagia at presentation. 47.88% had well differentiated carcinoma. Vitamin D estimation showed that among cases 58.2% were deficient compared to controls where levels were 66.2.This difference was statistically significant. CONCLUSION: It seems vitamin D deficiency does not play significant role in development of esophageal cancer. However, when vitamin D supplement was given to deficient/ insufficient patients prior to specific treatment we found that they did better in terms of improvement in dysphagia, loco-regional control and response.